Математичне моделювання коливань спеціалізованого транспортного засобу з дворівневою нелінійною системою підресорювання при переїзді одиничної дорожньої нерівності - Кайдалов, Руслан Олегович; Баштовий, Володимир Михайлович; Ларін, Олексій Олександрович; Водка, Олексій Олександрович; Баркалов, В. Г. (Харківський університет Повітряних Сил ім. Івана Кожедуба, 2016)
Стаття присвячена вивченню ефективності застосування нелінійного дворівневого підресорювання спеціальних транспортних засобів, яке спрямоване на підвищення плавності їх ходу. Наведені результати теоретичних досліджень, щодо характеристик відповідного транспортного засобу, як нелінійної системи. Побудовано математичну нелінійну дискретну динамічну модель даного транспортного засобу, на основі якої проведено серію досліджень щодо вільних коливань транспортного засобу. Наведено результати порівняльного аналізу щодо частот та амплітуд коливань які встановлюються в транспортному засобі в лінійній та запропонованій дворівневій нелінійній компоновках при імпульсному збудженні, що прикладається до коліс даного транспортного засобу.

The work deals with the definition of an effective way of the suspension on the specialized vehicles and is aimed on improvement of the smoothness of its movement (riding comfort). A riding comfort is an important operational feature of the modern vehicles that allow to protect the passengers and goods from the influence of the vibrations during the vehicle movement. These are especially important for the transportation of the dangerous goods. The paper presents the design scheme of specialized vehicles, which has additional level of cushioning, with the nonlinear characteristic, which has a quasi-zero stiffness in the equilibrium position. The mathematical model of the dynamic behavior of the specialized vehicles are developed as a nonlinear discrete system. The results of numeric calculations of the dynamic response of the vehicle on the impact is presented based on the developed model. A vertical vibrations of the luggage platform is analyzed caused by the kinematics impact that applied on the axis of the vehicle. The load is applied on the axis of the vehicle with time delay providing its vertical vibrations. The results of the comparative analysis is shown for the frequencies and amplitudes of the vehicle vertical vibrations within two different suspensions: in the linear and nonlinear statements under impact excitation.
Mathematical modeling of the vibration characteristics of a specialized vehicle with a double-leveled system of nonlinear suspension moving thru the unit road irregularity
Keywords: плавність ходу; нелінійне підресорювання; системи із квазінульовою жорсткістю; вільні коливання; ride smoothness; nonlinear suspension; systems with quasi-zero stiffness; nonlinear free oscillations